Early Mentions of Korea in British Parliamentary Debates - Sweeney, Loughlin J. (Korea observer, 2017)
In the late nineteenth century, Korea was at the nexus of Great Power contestation in East Asia. Having existed within the sphere of China for centuries, it found itself the subject of expansionary ambitions by the Russian and Japanese empires, and also drawn, in a limited way, into the sphere of Britain's informal empire. This paper discusses the extent to which a Korean dimension was incorporated into British parliamentary discourse in this period. It analyzes the Korean issues that captured the attention of British MPs, and examines the extent of their knowledge of Korean affairs in the late nineteenth century. It also considers the relevance of concepts of 'informal empire' and the 'official mind' to the discussion of East Asian imperial and geopolitical history in the late nineteenth century.